THE EARTH TECTONOSPHERE. NEW CONCEPT - Pushcharovskiy Yu.M. (My University, 2000)
At the present time the tectonosphere, as the region of tectonic movements, is restricted by the upper mantle, that is, by the depth of 670 km. The deeper geospheres are supposed to be tectonically inert. It is proved in this paper that the tectonosphere embraces the whole of the mantle up to its contact with the Earth core, residing at a depth of 2900 km. The basis for this conclusion was the analysis of the heterogeneities discovered by seismic tomography. The laterally traced high-velocity heterogeneities are interpreted as the zones of tectonic rock mass crowding, resulting from the movements of these rock masses along subhorizontal faults or from the processes of tectonic flow. The models offered in this paper change substantially the modern concepts of the deep Earth kinematics.
Keywords: EARTH TECTONOSPHERE; TECTONIC MOVEMENTS; UPPER MANTLE; HIGH-VELOCITY HETEROGENEITIES